Modeling subjective well-being in individuals with chronic pain and a physical disability: the role of pain control and pain catastrophizing. Issue 5 (27th February 2019) - Furrer, Angela; Michel, Gisela; Terrill, Alexandra L.; Jensen, Mark P.; Müller, Rachel
Abstract: Purpose: To investigate the associations between subjective well-being and pain intensity, pain interference, and depression in individuals with physical disabilities. We hypothesized that (1) pain control and (2) pain catastrophizing mediate the effects of subjective well-being on pain intensity, pain interference, and depression. Methods: Analyses of cross-sectional data from 96 individuals diagnosed with spinal cord injury, multiple sclerosis, neuromuscular disease, or post-polio syndrome, with average pain intensity of ≥4 (0–10) on at least half the days in the past month. Two models tested study hypotheses using structural equation. Results: Both models showed acceptable model fit. Pain catastrophizing significantly mediated the effect of subjective well-being on pain intensity and pain interference, but not on depression. Pain control did not significantly mediate the effect of subjective well-being on pain intensity, pain interference, or depression. Path coefficients showed significant direct effects of subjective well-being on pain control (β = 0.39), pain catastrophizing (β = −0.61), pain interference (β = −0.48; −0.42), and depression (β = −0.75; −0.78). Conclusions: This study supports the potential of enhancing subjective well-being and lowering pain catastrophizing for reducing pain intensity, pain interference, and depressive symptoms in individuals with chronic pain and a physical disability. The findings indicate that true experiments to test for causal associations are warranted. Implications for rehabilitation: The majority of individuals with physical disabilities report having persistent moderate-to-severe pain that may negatively limit daily activities and quality of life. The present cross-sectional study indicates that individuals who reported greater subjective well-being showed significantly lower pain intensity via the mediating effect of lower pain catastrophizing. Since sample size and respective power are low, these findings should be taken as first indications of potential underlying mechanisms between subjective well-being and pain outcomes that need further confirmation in longitudinal research. However, the findings suggest that treatments which enhance subjective well-being (increasing positive affect and life satisfaction, and decreasing negative affect, e.g., via positive psychology exercises) and reducing pain catastrophizing (via e.g., cognitive-behavioral therapy) may have the highest potential for benefiting individuals with disability-associated chronic pain.